2022
DOI: 10.1186/s12989-022-00453-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to polystyrene microplastics induced male reproductive toxicity and decreased testosterone levels via the LH-mediated LHR/cAMP/PKA/StAR pathway

Abstract: Background Microplastics (MPs), which are smaller in size and difficult to degrade, can be easily ingested by marine life and enter mammals through the food chain. Our previous study demonstrated that following acute exposure to MPs, the serum testosterone content reduced and sperm quality declined, resulting in male reproductive dysfunction in mice. However, the toxic effect of long-term exposure to MPs at environmental exposure levels on the reproductive system of mammals remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(55 citation statements)
references
References 57 publications
5
49
1
Order By: Relevance
“…Because the mice used in this study were from the same batch as those used in our previous study, refer to the previous article for the data regarding water intake, food intake, and body weight. 35 According to our previous measurements, 35 the water intake of each control mouse was about . The total exposure to PS-MPs was therefore and at 100 and , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Because the mice used in this study were from the same batch as those used in our previous study, refer to the previous article for the data regarding water intake, food intake, and body weight. 35 According to our previous measurements, 35 the water intake of each control mouse was about . The total exposure to PS-MPs was therefore and at 100 and , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The steroidogenic enzymes P450scc, P450c17, 3β-HSD, and 17β-HSD are involved in testosterone synthesis in Leydig’s cells ( Sun et al, 2019 ). Jin et al reported that administration of 100 and 1,000 μg/L of PS-MPs (0.5, 4, and 10 μm) in mice with drinking water for 180 days had shown a significant decrease in steroidogenic enzymes and steroidogenic acute regulatory protein (StAR) levels ( Jin et al, 2022 ). MPs may also cause morphological changes in sperm, such as absent and small head and acrosome loss ( Jin et al, 2022 ).…”
Section: Reproductive Toxic Effects Of Mps Exposurementioning
confidence: 99%
“…Jin et al reported that administration of 100 and 1,000 μg/L of PS-MPs (0.5, 4, and 10 μm) in mice with drinking water for 180 days had shown a significant decrease in steroidogenic enzymes and steroidogenic acute regulatory protein (StAR) levels ( Jin et al, 2022 ). MPs may also cause morphological changes in sperm, such as absent and small head and acrosome loss ( Jin et al, 2022 ). A repeated oral toxicity study for 28 days in SD rats has shown that PP-MPs induce lesions in the testis and epididymis at 25 mg/kg/day ( Jin et al, 2022 ).…”
Section: Reproductive Toxic Effects Of Mps Exposurementioning
confidence: 99%
See 2 more Smart Citations